Manajemen Pengelolaan Dana Desa - Arna Suryani (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research aims to describe, know and analyze management of village funds management. Management of village Funds management is measured through planning, implementation, supervision and responsibility or reporting. The research was conducted in Sungai Gelam village, Muaro District, Padang Gelam District. The type of data used in this study is primary data and secondary data. Data collection techniques are done triangulated (combined) i.e. observation, interviews, libraries, and documentation. This research is descriptive using a qualitative approach and the analysis is inductive or qualitative. Based on the results of the research of all processes in the management phases of the village fund management has been implemented, but the results for the planning and implementation process are still not optimal. This can be seen from the difference between the village's income budget and the realization of the village's income, where the realization of the village revenue is smaller than the planned village's income budget, as well as the amount of the village expenditure is not clear Thus grouped into other unexpected shopping fields. The amount of realization of village expenditure is greater than the amount of village revenue resulting in excess village expenditure. At the supervision and accountability stage or report the village funds is good enough. Local government support as well as human resources owned are supporting factors in conducting good Village fund management management. While the inhibitory factor is the concern for the planning between the village and the subdistrict is still not in sync, still the low allocation of village funds to support the operation of village governance and lack of socialization about the management of village funds to the village community.